2009
DOI: 10.1177/0022034509337146
|View full text |Cite
|
Sign up to set email alerts
|

Degradation-stage Effect of Self-etching Primer on Dentin Bond Durability

Abstract: It is well-known that self-etching primers can be altered. However, the effects from altered primers on the dentin bond durability have yet to be thoroughly identified. In this study, we examined the effects from 5 altered Liquid A primers in different stages of degradation-where 2-hydroxyethylmethacrylate (HEMA) and 10-methacryloyloxydecyl dihydrogen phosphate (MDP), used in Liquid A primers, were altered by the hydrolysis of the methacryloxy ester portion in the HEMA and MDP-on the hybrid layer's quality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…It has been reported that the shelf life stability problem of adhesives is not limited to acidic functional monomers; HEMA is also prone to degradation. 17 This monomer acts as a wetting agent that helps resin monomers diffuse into the dentin substrate and it has an ability to react with collagen fibrils. Hydrolysis of the monomers changes their chemical composition, leading to loss of their clinical function with prolonged storage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the shelf life stability problem of adhesives is not limited to acidic functional monomers; HEMA is also prone to degradation. 17 This monomer acts as a wetting agent that helps resin monomers diffuse into the dentin substrate and it has an ability to react with collagen fibrils. Hydrolysis of the monomers changes their chemical composition, leading to loss of their clinical function with prolonged storage.…”
Section: Discussionmentioning
confidence: 99%
“…Significance for all statistical tests was predominately at p<0.05. Figures 2, 3 and 4 show the expanded 13 C NMR spectra of the carbonyl and methylene regions of the designed MEP-NMGly, MDP-NMGly and NMEP-NMGly primers under different storage period conditions, and the NMR peak assignments of the carbons attributed to each acidic methacrylate monomer, NMGly and by-products, as produced by the hydrolysis of these monomers, respectively [3][4][5][6][7][8][9]11) . As shown in Figure 2, when the MEP-NMGly primer, which utilized a water-soluble acidic methacryl ester monomer, MEP, was altered, new NMR peaks, assigned to the methacrylic acid, MA (NMR peaks "α" 73 ppm]) were detected.…”
Section: Classification Of the Type Of Fracture Mode Of The Debonded mentioning
confidence: 99%
“…This decrease might be due to the produced byproducts that resulted in a decrease in the quality of the hybrid layer created at the resin-dentin interface 3,4) . However, further decreases in the mean bond strength were not observed, even though the MEP had completely hydrolyzed and the amounts of produced EG and phosphoric acid had increased (storage period=14 weeks).…”
Section: Effects From the Storage Periods Of The Nmgly-based Self-etcmentioning
confidence: 99%
See 2 more Smart Citations